Strategi persaingan provider telekomunikasi berdasarkan kriteria kepuasan pelanggan - Tyasti, Avia Enggar; Hayati, Dahliyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the level of customer satisfaction using the six sigma method which is an approach to reduce process variability through statistical tools. Industry 4.0 brings its own challenges for telecommunication providers. In the Industrial Era 4.0, which is marked by the integration between machine systems and smart internet, making dependence on telecommunication providers increases. Industrial companies currently compete in offering products in the form of goods or services in order to attract consumers' interest, as well as the telecommunications industry such as Indosat and Telkomsel. In recent years, providers from Indosat and Telkomsel have been in the top two rankings in terms of number of subscribers and profit generated. The highest DPMO value obtained from the Assurance dimension with a satisfaction target of 6. The results of the Assurance dimension DPMO for Indosat providers are 243.333.33 and Telkomsel providers are 224.166.67 and are at level 2 sigma. These results are still far from the expected target of 3.4 DPMO and 6-sigma